(untitled) (Revista Electrónica Calidad en la Educación Superior, 2019)
This article explores the teaching self-perception of the Administration Chair of the School of Management Sciences (ECA), linked to the Written Material Production Program (Promade) of the Directorate of Production of Teaching Materials (DPMD), of the State University Distance from Costa Rica. The interest is focused on quantifying the level of development reached by teachers in pedagogical mediation and digital competences both allow them to face technological and communication changes to integrate them into learning processes and thus apply a set of skills in the elaboration of didactic materials; this research is of a qualitative approach of the non-experimental exploratory type. The questionnaires showed the level of maturity of the teachers and the opportunities for improvement in the continuous training in the disciplines of technology, communication and pedagogical mediation. The collection of the data established those elements that reflect the quality in the elaboration of the didactic materials, it also establishes the skills required in the teachers under the distance modality. The positive results allow compliance with the scope of the guidelines of the strategic plan related to promoting teacher training, the development of digital materials with academic activities mediated by ICT, for hybrid subjects or 100% virtual in the Moodle institutional work platform.